Advanced Concepts for Intelligent Vision Systems: 17th International Conference, ACIVS 2016, Lecce, Italy, October 24-27, 2016, Proceedings - Blanc-Talon, Jacques; Distante, Cosimo; Philips, Wilfried; Popescu, Dan; Scheunders, Paul (LNCS sublibrary. SL 6, Image processing, computer vision, pattern recognition, and graphics, 2016)
This book constitutes the refereed proceedings of the 17th International Conference on Advanced Concepts for Intelligent Vision Systems, ACIVS 2016, held in Lecce, Italy, in October 2016.The 64 revised full papers presented in this volume were carefully selected from 137 submissions. They deal with classical low-level image processing techniques; image and video compression; 3D; security and forensics; and evaluation methodologies.